PERANCANGAN SISTEM INFORMASI PENYEWAAN KAMAR GUEST HOUSE TERAS SOLO - Setiawan, Setiawan; Sungkar, Hariz Muhammad (JURNAL LENTERA ICT, 2019)
Computerized system is one of the most important elements in a company, because a computerized system can improve or simplify the process of renting and servicing. At this time the room rental process that is happening at the Teras Solo Guest House, is still using a desktop-based application system. Where that can mean compiling a new system to replace the old system or improve the existing system of systems in a company, so we need a system that can solve problems faced such as checking data and making tenant data reports can not be done online. So the authors make a computerized system design ranging from renting and leasing room transaction processes and making reports, using the PHP web base program as a medium for designing the system. With this system, the author is expected to be implemented in the Teras Solo Guest House as a tool to solve the constraints of a desktop-based system which cannot yet be accessed on-line.Keywords: Computerized Systems, Online Rentals